Learning Facilities in Supporting the Process Learning and Learning Motivation - Dila Frameiliada; Soni Setiawan; Tamara Azizah; Kruger Margarida (Yayasan Adra Karima Hubbi, 2023)
Learning facilities are facilities and infrastructure that help facilitate the learning process to acquire knowledge at school so that learning objectives are achieved. The availability of complete learning facilities in schools facilitates students in the learning process. Learning facilities that must be provided in schools are buildings, classrooms, laboratories, libraries, BP rooms, and textbooks, where these types of facilities are facilities to support the learning process. The learning process is a sequence of changes because there is a process of interaction between students and educators and learning resources in a learning environment. Three main factors influence the learning process in the classroom, namely educators, students, and the classroom environment.